P207 Syphilis: significant increase in men who have sex with men (msm) since november 2013. (18th May 2015) - Pinto-Sander, Nicolas; Youssef, Elaney; Tweed, Marc; Dean, Gillian; Richardson, Daniel
Abstract : Background: High rates of infectious syphilis have been reported in MSM. Locally 1:10 of the population are estimated MSM and high rates of HIV and sexually transmitted infections are seen. Methods: We identified cases of infectious syphilis in MSM per month from February-2013 to June-2014 attending sexual health services. Age, ethnicity, HIV status and syphilis re-infection were noted. The total number of MSM seen in sexual health was used as a denominator for incidence calculations and rates were compared using Chi-square and Mann-Whitney test. Results: 207 new cases of infectious syphilis were identified over the study period. The median age was 36 years (19–60), 96/207(46.4%) were HIV+ and 3/207(1.4%) had syphilis re-infection. The median incidence of syphilis from February to October 2013 was 8.6/1000 MSM; this increased significantly to 25.9/1000 MSM from November–June 2014 [chi-square 67.447 (p < 0.0001). There was no significant difference in the percentage co-infected with HIV between these time points (February-October = 57%, November-June = 46% [Mann-Whitney = 16.5, p = 0.0581). Conclusion: We describe a significant increase in the incidence of infectious syphilis in MSM from November 2013. This rise is likely attributable to changes in sexual behaviour among MSM: increased accessibility to sex driven by social media, increased anonymous and group sex and growing use of party drugs. Locally we are working with the Terrence Higgins Trust and public health teams to increase awareness among MSM and primary care.